RESULTS coaching the new essential for school leaders - Kee, Kathryn; Sage eBooks; National Staff Development Council (U.S.) (Thousand Oaks, Calif. : Corwin ; London : SAGE [distributor], 2010)
Built upon the International Coaching Federation standards and competencies for coaching, this book introduces leaders to results coaching, a model that provides a navigation system for impacting new thinking and solution finding at every level of school systems.
Published in association with the National Staff Development Council.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Educational leadership -- United States; Personal coaching -- United States; Teachers -- In-service training -- United States; School administrators -- In-service training -- United States; School improvement programs -- United States; Electronic books